Studi Cakupan Wilayah Pelayanan Fasilitas Niaga di Kelurahan Pinang Kencana, Kota Tanjungpinang - Aria Bagiasa Chidmahdjati; Hoki Apriyenson; Arie Afriadi; Nefriwati Hilmi; Dea Rizky Saputri; Zuleriawati, A.S6 (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Commercial facilities such as supermarkets, minimarkets, and traditional stalls are an essential part of urban economic infrastructure services, especially in areas with high population growth. However, the rapid growth of population is not always balanced by an even distribution of commercial facilities. This triggers spatial accessibility inequality. This study aims to analyze the coverage of service areas of the three categories of commercial facilities in Pinang Kencana sub-district, Tanjungpinang City, using a spatial approach based on GIS. The methods employed include network analysis, service area analysis, and Euclidean distance analysis. The results of the study show that the coverage of 0-2,000 meters is an area served by all types of commercial facilities, with an area of 82.5%, while the area beyond 2,000 meters, which accounts for 17.5%, is an unserved area located in the east and southeast. The served zone is characterized by agglomerated residential areas, which have an adequate road network. In contrast, the unserved area is marked by limited road networks and low residential density. This research has strategic implications for policymakers, especially in preparing zoning regulations and Detailed Spatial Planning Plans (RDTR) in Pinang Kencana sub-district, East Tanjungpinang District, Tanjungpinang City.